Clinical Characteristics and Early Visual Outcomes of Highly Myopic Cataract Eyes: The Shanghai High Myopia Study - He, Wenwen; Yao, Yunqian; Zhang, Keke; Du, Yu; Qi, Jiao; Zhang, Yinglei; Zhang, Shaohua; Zhao, Zhennan; Cai, Lei; Fan, Qi; Jiang, Yongxiang; Yang, Jin; et al. (Frontiers in Medicine, 2022)
Purpose: To report ocular characteristics and early visual outcomes of highly myopic cataract eyes, and to analyze the risk factors of low vision. Methods: A total of 2027 eyes of 1400 cataract patients with axial length (AL)≥26mm undergoing cataract surgery in Eye & ENT Hospital of Fudan University, who were registered in the Shanghai High Myopia Study, were analyzed. Routine preoperative ophthalmic examinations were performed and macular scan of optical coherence tomography (OCT) were obtained. Macular complications, central foveal thickness (CFT) and subfoveal choroidal thickness (SFCT) were evaluated from OCT images. Ocular and surgical history and perioperative complications were also recorded. Uncorrected and best-corrected visual acuity (UCVA/BCVA) 1 month postoperatively and its influencing factors were evaluated. Results: Of the involved eyes, the average AL was 29.52 ± 2.26mm, and 39.7% were with an AL>30mm and 26.4% were with a corneal astigmatism more than 1.5D, and nuclear cataract accounted for the largest proportion (70.6%). The rate of overall macular complications was 27.6%. Postoperative UCVA and BCVA were 0.70 ± 0.46 and 0.25 ± 0.32 logMAR, respectively. BCVA improved significantly (vs P<0.001) and became worse with the elongation of AL (P<0.001) and thinning of CFT and SFCT (both P<0.001). The risk factors of postoperative low vision (BCVA<20/66) were macular atrophy, lamellar macular hole, high corneal astigmatism, long AL, thin SFCT and junior surgeons, odds ratios ranging from 1.54 to 54.87 (all P<0.05). Conclusion: Cataract surgery could improve the VA of highly myopic eyes. Eye with macular complications, higher corneal astigmatism, longer AL, thinner SFCT, and who is treated by a junior surgeon, may have a high risk of low vision after surgery.